1998
DOI: 10.7202/005296ar
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of White-Collar Compensation and Organizational Performance

Abstract: Volume 53, numéro 3, été 1998 URI : id.erudit.org/iderudit/005296ar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…However, it can be said that our results are generally in line with the earlier findings of the literature on performance evaluation in incentive plans. For example, our finding that PRP payments account for a higher share of total earnings for white‐collar employees than for blue‐collar workers supports the results by O’Shaughnessy (1998), who concluded that the relationship between the bonus to base ratio and performance is stronger higher in the organizational hierarchy. Furthermore, the results of Murphy (1999, 2000) show that in executive incentive contracts, typically (1) the performance measures include a measure of profitability, (2) multiple measures are used, and (3) bonuses are capped.…”
Section: Resultssupporting
confidence: 88%
“…However, it can be said that our results are generally in line with the earlier findings of the literature on performance evaluation in incentive plans. For example, our finding that PRP payments account for a higher share of total earnings for white‐collar employees than for blue‐collar workers supports the results by O’Shaughnessy (1998), who concluded that the relationship between the bonus to base ratio and performance is stronger higher in the organizational hierarchy. Furthermore, the results of Murphy (1999, 2000) show that in executive incentive contracts, typically (1) the performance measures include a measure of profitability, (2) multiple measures are used, and (3) bonuses are capped.…”
Section: Resultssupporting
confidence: 88%
“…Because WCEs are neither blue-collar workers (BCEs), who exert substantial physical effort in their routine tasks, nor top management, possessing extensive decision rights, the performance effects of incentive systems for WCEs still remain an unexplored empirical topic (e.g. Belfield and Marsden 2003;Kauhanen and Piekkola, 2006;O'Shaughnessy 1998). Given the central role of financial incentives in organizational functioning and for employees at lower hierarchical levels (Kihn, 2007;Du, Deloof and Jorissen, 2013), research is needed on the association between incentives at lower hierarchical levels and firm performance.…”
Section: Introductionmentioning
confidence: 99%